Effect Analysis of the V-Angle and Straight Edge Length on the Performance of V-Shaped Blades for a Savonius Hydrokinetic Turbine - Bohan Wang; Xu Bai; Guoqiang Lei; Wen Zhang; Renwei Ji (Journal of Marine Science and Engineering)
This study investigated the performance of Savonius hydrokinetic turbine blades through three-dimensional computational fluid dynamics simulations conducted at a fixed tip speed ratio of 0.87. A multi-factor experimental design was employed to construct 45 V-shaped rotor blade models, systematically examining the effects of a V-angle (30–140°) and straight-edge length (0.24 L–0.62 L) on hydrodynamic performance, where L = 25.46 mm (the baseline length of the straight edge). The results indicate that, as the V-angle and the straight-edge length vary independently, the performance of each blade first increases and then decreases. At TSR = 0.87, the maximum power coefficient (CP) of 0.2345 is achieved by the blade with a 70° V-Angle and a straight edge length of 0.335 L. Pressure and velocity field analyses reveal that appropriate geometric adjustments can optimize the high-pressure zone on the advancing blade and suppress negative torque on the returning blade, thereby increasing net output. The influence mechanisms of the V-angle and straight-edge length variations on blade performance were further explored and summarized through a comparative analysis of the vorticity characteristics. This study established a detailed performance dataset, providing theoretical and empirical support for V-shaped rotor blade design studies and offering engineering guidance for the effective use of low-flow hydropower.